Elastic Analysis for a Finite Cracked Plate of Functionally Graded Materials - Chen, Y.Z; Lin, X.Y (Multidiscipline modeling in materials and structures, 2007)
In this paper, elastic analysis for an edge-cracked plate of functionally graded materials (FGMs) is carried out. The cracked plate is subject to a longitudinal tension. The property of FGMs is assumed to be exponential function form in both x- and y-directions. The finite element method is suggested to solve the boundary value problem. An indirect method, the energy release method, is developed to evaluate the stress intensity factors (SIFs) at the crack tip. Under the applied loading, the amount of the release energy from the crack length "a" to " a + a " can be evaluated from relevant displacements at the top face of plate. The SIFs can be obtained from a relation between the energy release rate and SIF. The obtained result shows that the property of FGMs has a significant influence to the value of SIF at crack tip. Numerical results are given which are useful for engineer to assess the safety of the cracked plate of FGMs.